Sexual Enhancing Effect of Anacardium occidentale in Stress-Exposed Rats by Improving Dopaminergic and Testicular Functions. (25th October 2018) - Wattanathorn, Jintanaporn; Prabsattroo, Thawatchai; Somsapt, Pichet; Sritragool, Opass; Thukham-mee, Wipawee; Muchimapura, Supaporn
Abstract : In this study, we aimed to assess the effect and possible underlying mechanism of Anacardium occidentale leaves extract on male sexual behaviors in stress-exposed rats. Male Wistar rats were orally given A. occidentale extract at doses of 25, 100, and 200 mg/kg BW before 12-hour-immobilization exposure for 14 days. Sexual behaviors, serum testosterone and corticosterone levels, TH-positive cells density in nucleus accumbens (NAc) and ventral tegmental area (VTA), MAO-B activity in NAc and medial preoptic area (MPOA), testis histology together with phosphodiesterase type-5 ( PDE-5) activity, and endothelial nitric oxide synthase (eNOS) expression in penis were evaluated after treatment. All doses of extract improved male sexual behaviors, suppressed MAO-B in NAc, enhanced TH-positive cells density in NAc, suppressed PDE-5 in penis, and enhanced interstitial cell of Leydig. The increase of serum testosterone, TH-positive cells density in VTA, eNOS expression in penis, and the decreased serum corticosterone were observed at some doses. Therefore, the sexual enhancing effect of extract occurred mainly via the improved dopaminergic and testicular functions. PDE-5 suppression in penis also played the role especially in the increased intromission behavior. Therefore, A. occidentale leaves extract is the potential protective agent against sexual dysfunction. However, further researches are necessary.